Deciphering Consumer Aspirations: A Search Engine Analysis to Long-Tail Keyword in Entrepreneurship - Asep Koswara Asep Koswara; Neni Kurniawati (Journal of Strategic Innovation and Business Management, 2026)
This study investigates how long-tail search engine keywords represent consumer aspirations and early-stage entrepreneurial cognition by examining Indonesian search queries derived from the primary term “ide usaha.” Employing a search engine analysis approach supported by Python-based data visualization, the research analyzes how prospective entrepreneurs articulate feasibility concerns, contextual limitations, and growth-oriented expectations through extended keyword constructions. The findings demonstrate that long-tail keywords operate as meaningful signals of entrepreneurial aspiration rather than merely technical SEO components. Observed search patterns reveal pronounced tendencies toward risk minimization, capital sensitivity, and preference for digital and home-based business models, while simultaneously expressing ambitions related to profitability, sustainability, and differentiation. The study contributes theoretically by conceptualizing opportunity recognition as a digitally mediated and cognitively iterative process traceable through online search behavior. Methodologically, it highlights the potential of digital trace data as a scalable, unobtrusive approach to examining entrepreneurial intention formation. Practically, the findings provide actionable insights for educators, policymakers, and digital platform designers seeking to align entrepreneurial support systems with authentic aspirations reflected in real-world search activity.